HOW SHOULD THE CLASSROOM BE MANAGED DURING THE COVID-19 PANDEMIC? - Tyas, E. Handayani; Naibaho, Lamhot (International Journal of Research -GRANTHAALAYAH, 2021)
This study is about classroom management during the Covid-19 Pandemic. This study aims to find out how the classroom should be managed during the Covid-19 Pandemic. It was done at Universitas Kristen Indonesia within three months, from February – April 2021. The method of the study is library research, where the researchers were the instruments of this study. To answer the problem of the study, the researchers collect some documents related to school management taken from online and printed journals, books, articles. The documents analyzed to provide the answers to this study were taken from the library and Google Scholar. The result of this study is that good and correct management requires commitment from all elements involved in school management, parents of students and community members who are members of the school committee, and the community in the school environment during the Covid-19 Pandemic. To run the school management smoothly, the leadership must apply the principles of transparency and professionalism. So it is concluded that those involved in the school management should cooperate, and transparency and professionalism should be implemented during the Covid-19 Pandemic.